Lecturer Strategies in Delivering Knowledge to Students at STAIN Mandailing Natal North Sumatera - Kholidah Nur (Budapest International Research and Critics University, 2020)
Class management strategies are part of Education Management which more specifically emphasizes the ability or competence of lecturers in creating conducive learning in the classroom. This research is intended to find out how the Lecturer Strategy in Conveying Knowledge. From here, the lecturers' strategies in class will be found related to spatial planning, determining learning time, determining the source of teaching materials, creating interactions with students and creating student discipline in the classroom. This research is a field research (observation) and the data used consists of interviews, observation and documentation. The approach used in this research is qualitative. This approach is used to fully find out what strategies the lecturer has implemented in creating effective and efficient learning. By using Maslow's theory to identify a person's needs or motives in carrying out activities, while Herzberg focuses on activity satisfaction (achievement) which will motivate someone to carry out Classroom Management Effectiveness activities.